Acute venous thromboembolism and return to intercollegiate athletics: A case review - Newsham, K. R.; Cobb, M.; Bayes, M. (International Journal of Athletic Therapy & Training, 2014)
The article present a case study of a 20-year-old female softball player that was admitted to the emergency department due to the acute shortness of breath and severe chest pain. The computed tomography of her chest was done which shows extensive pulmonary emboli and she was treated with subcutaneous thrombolytics along with enoxaparin sodium. The article discusses the risk factors of venous thromboembolism including endothelial injury, immobilization and oral contraceptives.